2013
DOI: 10.3920/bm2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of functional properties of lactic acid bacteria isolated from faecal microbiota of healthy dogs for potential use as probiotics

Abstract: Lactic acid bacteria were isolated and identified in the faeces of Chinese Crested and Yorkshire terrier pups and their probiotic features were investigated in vitro. Thirty seven isolates were identified as Lactobacillus or Enterococcus. Out of these isolates, 31 were lactic acid bacteria (LAB) and belonged to the species Lactobacillus reuteri (16/37; 43.3%), Lactobacillus animalis (7/37; 18.9%), Lactobacillus acidophilus (3/37; 8.1%), Lactobacillus sanfranciscensis (2/37; 5.4%), Lactobacillus murinus (2/37; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…The inhibition zones were large and clear against the reference strains of E. coli (ATCC 25922), K. pneumoniae (ATCC 700603), S. typhimurium (MTCC 3231) and S. enteritidis (ATCC 13076) but limited and hazy zones were observed against Enterobacter species. Silva et al (2013) from Brazil reported promising in-vitro antibacterial activity in Lactobacillus isolates of dog faecal origin against E. coli and other pathogenic bacteria. Vineetha et al (2016) from India reported promising in-vitro antibacterial activity in Lactobacillus isolates of poultry faecal origin against E. coli, S. typhimurium and S. enteritidis.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition zones were large and clear against the reference strains of E. coli (ATCC 25922), K. pneumoniae (ATCC 700603), S. typhimurium (MTCC 3231) and S. enteritidis (ATCC 13076) but limited and hazy zones were observed against Enterobacter species. Silva et al (2013) from Brazil reported promising in-vitro antibacterial activity in Lactobacillus isolates of dog faecal origin against E. coli and other pathogenic bacteria. Vineetha et al (2016) from India reported promising in-vitro antibacterial activity in Lactobacillus isolates of poultry faecal origin against E. coli, S. typhimurium and S. enteritidis.…”
Section: Resultsmentioning
confidence: 99%
“…LAB intrinsically encoding resistance to oxacillin has also been well described in the literature, considering that this antimicrobial is not related to plasmid conjugation (Mathur and Singh ; Silva et al . ; Alvim et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus fermentum, Lactobacillus rhamnosus, and Lactobacillus salivarius are reported being a part of health canine intestine [13]. Other canine lactobacilli are represented by Lactobacillus murinus and Lactobacillus reuteri [12], Lactobacillus animalis, Lactobacillus sanfranciscensis and Lactobacillus paraplantarum [14].…”
Section: Canine and Feline Microbiotamentioning
confidence: 99%